고준위 방사성폐기물 처분장에서 벤토나이트 완충제에 대한 열-수리-화학 작용 개념 모델링 - 최병영; 류지훈; 박진영; Byoung-Young Choi; Ji-Hun Ryu; Jinyoung Park (Journal of nuclear fuel cycle and waste technology (Online), 2016)
본 연구에서는 벤토나이트의 변질을 모사하기 위해 TOUGHREACT를 이용하여 열-수리-화학적 개념 모델링을 수행하였다. 모델링 결과 벤토나이트의 포화도는 지속적으로 증가하여 약 10 년 후에 포화상태에 도달하였다. 또한 온도는 급격히 증가 하여 0.5 년 이후에는 구리관으로부터 거리에 따라 일정한 온도 구배가 유지되었다. 이러한 열-수리 조건 변화에 따라 화학 적으로는 경석고와 방해석의 변질이 주로 발생하였다. 경석고와 방해석은 지하수가 유입됨에 따라 지속적으로 용해되었으 나, 온도가 높은 구리관 인근에서는 침전하는 경향을 보여주었다. 또한 경석고와 방해석의 침전으로 인해 구리관 인근의 공 극률과 투과도가 감소하였다. 확산 상수 변화에 대한 모델링 결과 경석고와 방해석의 변질은 확산 상수에 매우 민감하였으 며, 이는 결과적으로 수리적 특성인 공극률과 투과도에 영향을 미치고 있었다. 본 연구는 고준위 방사성폐기물 처분장 안전 성 연구에 기초적인 자료를 제공해 줄 것으로 판단된다. In this study, thermal-hydrological-chemical modeling for the alteration of a bentonite buffer is carried out using a simulation code TOUGHREACT. The modeling results show that the water saturation of bentonite steadily increases and finally the bentonite is fully saturated after 10 years. In addition, the temperature rapidly increases and stabilizes after 0.5 year, exhibiting a constant thermal gradient as a function of distance from the copper tube. The change of thermal-hydrological conditions mainly results in the alteration of anhydrite and calcite. Anhydrite and calcite are dissolved along with the inflow of groundwater. They then tend to precipitate in the vicinity of the copper tube due to its high temperature. This behavior induces a slight decrease in porosity and permeability of bentonite near the copper tube. Furthermore, this study finds that the diffusion coefficient can significantly affect the alteration of anhydrite and calcite, which causes changes in the hydrological properties of bentonite such as porosity and permeability. This study may facilitate the safety assessment of high-level radioactive waste repositories.